Jurisdiksi International Criminal Court (ICC) Terhadap Presiden Rusia Vladimir Putin Berdasarkan Ketentuan Hukum Humaniter Internasional - Tuasalamony, Rauda Fil Jannah; Wattimena, Josina Augustina Yvonne; Anwar, Arman (PATTIMURA Law Study Review, 2025)
The International Criminal Court (ICC) is important in enforcing international law, especially against serious crimes. In March 2023 the ICC issued an arrest warrant for President Vladimir Putin regarding his crimes against humanity and war crimes, even though Russia is not a member country of the ICC. The issues in this writing include, whether Russian President Vladimir Putin can be arrested by the International ICC under the provisions of International Humanitarian Law and whether Russian President Vladimir Putin can be held accountable to the ICC under the provisions of International Humanitarian Law. The research method applied is normative legal research by studying legal library materials through statutory, case, and conceptual approaches and using quanlitative analysis. Research results show that the ICC has limited jurisdiction and cannot outperform national courts, it does not have the power to enforce arrest and accountability without Russia's cooperation. Russia also has veto rights at the UN, so Russia can use its veto rights to protect its national interests. Even though it is difficult for the ICC to arrest and hold Putin accountable, the arrest warrant affects Russia's political and diplomatic relations. The research aims to serve as input for legal science, especially in International Law related to the Arrest and Accountability of Russian President Vladimir Putin to the ICC Based on the Provisions of International Humanitarian Law.